Acute Effects of Dynamic Stretching Followed by Vibration Foam Rolling on Sports Performance of Badminton Athletes - Lin, Wei-Cheng (J Sports Sci Med, 2020)
Dynamic stretching (DS) is performed to increase sports performance and is also used primarily for transiently increasing range of motion (ROM). Recently, vibration foam rolling (VFR) has emerged. Its underlying concept is that it combines foam rolling techniques with local vibration to improve ROM and muscular activation concurrently. This crossover study investigated the effects of DS or DS followed by VFR (DS + VFR) during warm-ups on flexibility, muscle stiffness, power, and agility of the lower limbs in badminton athletes. Forty badminton players performed DS or DS + VFR as warm-up exercises on two occasions in a randomized order. The target muscle groups were the bilateral shoulder, anterior and posterior thigh, posterior calf, and lower back. Main outcome measures: The primary outcome was knee range of motion (ROM), and the secondary outcomes were muscle stiffness, lower limb power (countermovement jump [CMJ]), and agility. Results indicated that the protocols improved performance. DS increased knee flexion ROM (% change = 1.92, ES = 0.3, p = 0.033), CMJ height (% change = 5.04, ES = 0.2, p = 0.004), and agility (% change = -4.97, ES = 0.4, p < 0.001) but increased quadriceps muscle stiffness (% change = 3.74, ES = 0.3, p = 0.001) and increased gastrocnemius muscle stiffness (% change = 10.39, ES = 0.5, p = 0.001). DS + VFR increased knee extension ROM (% change =2.87, ES = 0.4, p = 0.003), reduced quadriceps muscle stiffness (% change = -2.79, ES = 0.3, p = 0.017), CMJ height (% change = 2.41, ES = 0.1, p = 0.037), and agility (% change = -4.74, ES = 0.2, p < 0.001). DS + VFR was not significantly superior to DS, except for muscle stiffness reduction. Taken together, we suggest that practitioners consider DS as a first line of warm-up exercise to increase ROM, CMJ height, and agility in athletes. Moreover, the addition of VFR to DS results in a large reduction of muscle stiffness, potentially reducing the risk of sports injury. Athletes, coaches and athletic professionals may consider them when selecting effective warm-up practices to augment athletic performance.